Investigação Ambiental de Aspergillus spp. em Enfermaria de Onco-Hematologia de um Hospital de Referência do Mato Grosso do Sul - Ferreira, Suellen Raquel da Silva (2022)
Aspergillus species are ubiquitous opportunistic pathogens responsible for causing serious diseases. A. fumigatus is the agent most implicated in cases of invasive and chronic pulmonary aspergillosis (IA). Inhalation of spores is the main route of transmission of AI in immunocompromised patients. The identification of the fungus at the species level is complex. There are few fungal surveillance studies in the Midwest region of Brazil and environmental contamination is a risk condition for immunocompromised patients to acquire aspergillosis. The aim of this study was to investigate the presence, identify and determine the antifungal susceptibility of Aspergillus spp. isolated in the ambient air of the oncology-hematology ward of a tertiary hospital in Mato Grosso do Sul. From August 2019 to February 2020, 896 ambient air samples were taken (bedrooms and bathrooms). Air collection was performed with an air impactor (100L/min for 1 minute) containing dichloran rose bengal chloramphenicol agar plates. The plates were incubated for 72 h at 30°C. The fungi were identified through phenotypic (macroscopic and microscopic characteristics) and genotypic (PCR and sequencing) tests. The minimum inhibitory concentration (MIC) of the antifungals itraconazole, voriconazole, posaconazole and amphotericin B for A. fumigatus was determined by the broth microdilution test as recommended by EUCAST (doc. E.Def 9.3.2, EUCAST). 250 Aspergillus spp. of ambient air. Identification by sequencing was performed in 132 of the 250 isolates. The most prevalent species were Aspergillus fumigatus (66), A. flavus (14) and A. niger (11). Two A. fumigatus isolates were resistant to voriconazole (MIC = 2 mg/L) and 2 to posaconazole (MIC = 0.5-1 mg/L). All A. fumigatus isolates were sensitive to amphotericin B and itraconazole. The results obtained contribute to the knowledge of hospital fungal biodiversity in Brazil and provide subsidies for the implementation of measures to control fungal contamination through the air in wards where patients at high risk for invasive aspergillosis are found.